Seno valodu profesors Pauls Žibeiks un viņa metode (1987.-1992.) - Zeps, Dainis (My University, 2010)
Professor Pauls Žibeiks usually is mentioned as professor of Old Testament. In my memories P. Žibeiks takes place of the professor of ancient languages, which he taught in the theological seminary. During the period of time 1987-1992 I was in close touch with the professor, first being his student in his classes of ancient languages in the seminary rooms in Jāņa street, and after, visiting him in Bauska with certain regularity. Here, professor's Pauls Žibeiks teaching method is briefly considered in context of language teaching methods in the Rīga Domskola, the Theological faculty of University of Latvia and the Lutheran theological seminary.
Keywords: Profesors Pauls Žibeiks; Senebreju valoda - mācīšana; Senās valodas - pasniegšanu metodika; Rīgas domskola; LU teoloģijas fakultāte; Luterāņu teoloģijas seminārs